Immune evasion strategies of bovine viral diarrhea virus - Pang, Feng; Long, Qinqin; Wei, Min (Frontiers in Cellular and Infection Microbiology, 2023)
Bovine viral diarrhea virus (BVDV) is a significant pathogen that causes great economic losses in the global livestock industry. During the long-term interactions between BVDV and its hosts, the virus has evolved multiple strategies to evade the host’s innate immunity and adaptive immunity, thereby promoting viral survival and replication. This review focuses on the most recent research on immune evasion strategies employed by BVDV, including evading type I IFN signaling pathway, evading host adaptive immunity, mediating NF-κB signaling pathway, mediating cell apoptosis and inducing autophagy. Unraveling BVDV’s immune evasion strategies will enhance our understanding of the pathogenesis of BVDV and contribute to the development of more effective therapies for the prevention, control and eradication of BVDV.